2018
DOI: 10.2741/s512
|View full text |Cite
|
Sign up to set email alerts
|

Genetic organization of i Streptococcus salivarius i 24SMBc i blp i -like bacteriocin locus

Abstract: This strain has recently been found useful and widely applied as an oral probiotic in the prevention of recurrent characterization of showing a crucial role in interspecies competition within the nasopharynx. hypervariable region was specific target 24SMBc contribute to elucidate the microbial interactions in the nasopharynx, underlining the potential role of  the locus in human nasopharyngeal colonization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…S salivarius is an a-hemolytic streptococci and an early colonizer in the human airway. [26][27][28] The presence of S salivarius is suggestive of healthy airway flora with desirable characteristics, such as production of bacteriocin-like peptides and disruption of pathogenic biofilm formation. 28,29 The S salivarius abundance in the oropharyngeal microbiome of patients with severe asthma increased approximately 5 times after a 6-month treatment with azithromycin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S salivarius is an a-hemolytic streptococci and an early colonizer in the human airway. [26][27][28] The presence of S salivarius is suggestive of healthy airway flora with desirable characteristics, such as production of bacteriocin-like peptides and disruption of pathogenic biofilm formation. 28,29 The S salivarius abundance in the oropharyngeal microbiome of patients with severe asthma increased approximately 5 times after a 6-month treatment with azithromycin.…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28] The presence of S salivarius is suggestive of healthy airway flora with desirable characteristics, such as production of bacteriocin-like peptides and disruption of pathogenic biofilm formation. 28,29 The S salivarius abundance in the oropharyngeal microbiome of patients with severe asthma increased approximately 5 times after a 6-month treatment with azithromycin. 30 Azithromycin is a macrolide antibiotic with broad-spectrum activity against many microorganisms, suggesting the observed changes in S salivarius abundance in their study may result directly from antibacterial activity.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies shown that chemical interactions through secretion of molecules by different microbial species may affect spatial biofilm structure, regulating both its formation and dispersion [4143]. Recently, Santagati et al described the presence of a blpU-like bacteriocine cassette in the genome of S. salivarius 24SMB, which has been shown to mediate intra- and interspecies competition with inhibitory activity against S. pyogenes and S. pneumoniae and also to provide competitive advantage in colonization in vivo [15, 44]. However, no other genes responsible for production of bacteriocine (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…However, no other genes responsible for production of bacteriocine (i.e. salivaricins, commonly produced by other S. salivarius strains) were identified throughout the genome [15]. Similarly, S. oralis 89a possess a locus for the production of a Colicin V, a proteolitically processed peptide antibiotic, which kills sensitive cells by disrupting membrane potential [45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation